2015
DOI: 10.1109/tit.2015.2398436
|View full text |Cite
|
Sign up to set email alerts
|

High-Rate Quantum Low-Density Parity-Check Codes Assisted by Reliable Qubits

Abstract: Abstract-Quantum error correction is an important building block for reliable quantum information processing. A challenging hurdle in the theory of quantum error correction is that it is significantly more difficult to design error-correcting codes with desirable properties for quantum information processing than for traditional digital communications and computation. A typical obstacle to constructing a variety of strong quantum error-correcting codes is the complicated restrictions imposed on the structure o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Codes in [34] and [35] are derived from [36]. In the latter case, it is shown that the performance is close to conventional LDPC codes [37]. It is worth mentioning that the first authors of four references [34]- [37] are Japanese researchers.…”
Section: Quantum Ldpc Codesmentioning
confidence: 99%
See 1 more Smart Citation
“…Codes in [34] and [35] are derived from [36]. In the latter case, it is shown that the performance is close to conventional LDPC codes [37]. It is worth mentioning that the first authors of four references [34]- [37] are Japanese researchers.…”
Section: Quantum Ldpc Codesmentioning
confidence: 99%
“…To overcome this problem, a method of giving up the commutativity and using EA instead has been proposed [39]. This method has been reported to achieve high performance close to that of conventional LDPC codes [37].…”
Section: Quantum Ldpc Codesmentioning
confidence: 99%
“…We overcome these restrictions by finding an exact solution of a specific error correction strategy: a parity check error correction code [53][54][55] involving a single The input state ρ in , is composed of n sensing qubits and one ancillary qubit. The sensing qubits evolve according to the signal ω and noise γ.…”
Section: Error Correction Enhanced Quantum Metrologymentioning
confidence: 99%
“…In the last few years, more sophisticated schemes have been proposed. Fujiwara et al noted that measuring more than a minimal set of stabilizers could be a more efficient way to extract reliable information and noted a possible connection to designs [5,6]. Ashikmin et al generalized existence theorems and the quantum Singleton bound of standard quantum error correction (QEC) theory so that they take into account redundancy in measurements [7].…”
Section: Introductionmentioning
confidence: 99%